2008
DOI: 10.1038/ki.2008.392
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of urea transporter knockout mice shows renal pelvic abnormalities

Abstract: Many transgenic and knockout mouse models with increased urine flow have been noted to have structural abnormalities of the renal pelvis and renal inner medulla. Here, we describe an approach for in vivo study of such abnormalities in mice using high resolution contrast enhanced T1-weighted magnetic resonance imaging (MRI). The studies were carried out in mice in which the UT-A isoform 1 and 3 urea transporters had been deleted (UT-A1/3-/- mice). The experiments revealed three distinct variations in the appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Since chronic stimulation of GPCRs is known to trigger multiple cellular events that dampen tissue responses in the continued presence of an activating ligand (receptor desensitization), one possibility is that receptor desensitization events are responsible for the observation that the ONO effects on urine osmolality were reduced at later time points ( Figure 5D). To determine whether prolonged ONO treatment had any effect on the pathological changes in kidney morphology usually associated with XNDI, we employed MRI that relies on the ability of a chelated gadolinium contrast agent to accumulate in the urinary space (21). V2R fl/y Esr1-Cre mice received either vehicle or ONO (55 μg/d/mouse) via s.c. infusion for 2 weeks using osmotic minipumps.…”
Section: Figurementioning
confidence: 99%
“…Since chronic stimulation of GPCRs is known to trigger multiple cellular events that dampen tissue responses in the continued presence of an activating ligand (receptor desensitization), one possibility is that receptor desensitization events are responsible for the observation that the ONO effects on urine osmolality were reduced at later time points ( Figure 5D). To determine whether prolonged ONO treatment had any effect on the pathological changes in kidney morphology usually associated with XNDI, we employed MRI that relies on the ability of a chelated gadolinium contrast agent to accumulate in the urinary space (21). V2R fl/y Esr1-Cre mice received either vehicle or ONO (55 μg/d/mouse) via s.c. infusion for 2 weeks using osmotic minipumps.…”
Section: Figurementioning
confidence: 99%
“…In addition, a number of SNPs have been identified in the UT-A gene that point to a possible relationship between polymorphisms in the UT-A gene and blood pressure regulation [88], giving credence to the idea that pharmacological manipulation of UT-A proteins can potentially be effective in treatment of water balance disorders and possible subsequent high blood pressure. However, in a recent study, UT-A1/3 −/− mice were reported to have a higher mean arterial blood pressure [89]. Whether this increased blood pressure is due directly to the loss of facilitative urea transporters or due to the subsequent renal pelvic abnormalities after prolonged diuresis remains to be determined.…”
Section: Clinical Perspectivementioning
confidence: 90%
“…Several knock-out mice lacking urea transporters, such as UT-A1 and UT-A3 (57), UT-A2 (8), UT-B1 (911), or UT-A2 and UT-B1 (12), have been generated and have decreased maximal urine concentrating ability, demonstrating that urea transporters play a major role in urinary concentration. They also raise the possibility that inhibition of urea transporters may be a target for the development of novel diuretics (urearetics).…”
Section: Introductionmentioning
confidence: 99%